Returning to care after incarceration with HIV: the French Guianese experience - F. Huber; S. Vandentorren; A. Merceron; T. Bonifay; A. Pastre; A. Lucarelli; M. Nacher (BMC, 2020)
Abstract Background HIV prevalence in correctional facilities may be 2 to 10 times higher than in the general adult population. Antiretroviral therapy (ART) interruption is frequent after an incarceration. This, in combination with post-release high-risk behaviors, may have detrimental consequences on the epidemic. Although return to care after release from correctional facilities has been described in many North American settings, data from South America seemed scarce. French Guiana is the only French territory located in South America. In 2014, HIV prevalence was estimated at 1.2% among pregnant women and oscillated around 4% in the only correctional facility. Method HIV-infected adults released from the French Guiana correctional facility between 2007 and 2013 were included in a retrospective cohort survey. The first objective was to describe the cascade of care in the 4 years following release. The secondary objectives were to describe contacts with care and to identify factors associated with return to HIV care, 1 year after release. Results We included 147 people, mostly males (81.6%). The median time before the first ambulatory consultation was 1.8 months. Within 1 year after release, 27.9% came for unscheduled emergency consultations, 22.4% were hospitalized. Within 4 years after release, 40.0-46.5% were in care, 22.4% archieved virological success. Being on ART when incarcerated was associated with HIV care (aIRR: 2.0, CI: 1.2-3.0), whereas being HIV-diagnosed during the last incarceration was associated with poor follow-up (aIRR: 0.3, CI: 0.1-0.9). Conclusion The risk of HIV-follow-up interruption is high, after an incarceration with HIV. ART supply should be sufficient to cover the timespan following release, several months if possible. Those not on ART at the time of incarceration may require special attention, especially those newly HIV-diagnosed while in custody. Comprehensive programs are necessary to support ex-offenders to stay on ART after incarceration.